SPECIFIC AND NON-SPECIFIC QUALITY PARAMETERS OF ETHANOL EXTRACT FROM MORINGA SEEDS (Moringa oleifera L.) - Dewi, Adellia Cindy Rosita; Dewi, Indri Kusuma (Jurnal Jamu Kusuma, 2025)
Moringa (Moringa oleifera L.) is one of the plants that has the potential and is used in traditional medicine. One of the parts of the moringa plant that can be used is moringa seeds, because it contains essential nutrients such as protein, vitamins A, B, K, C, as well as minerals such as calcium, magnesium and iron. In addition, moringa seed extract also has secondary metabolite compounds such as alkaloids, tannins, flavanoids and saponins that have the potential to be medicinal ingredients. This study aims to determine the test results of specific parameters including identity, organoleptic, dissolved compounds in water solvents, dissolved compounds in ethanol solvents and non-specific test results of extracts including moisture content, ash content, and insoluble acid ash content. The design used in this study is descriptive and the data analysis used is univariate analysis. Moringa seed ethanol extract (Moringa oleifera L.) was obtained by the extraction method for 5 days and then remacerated. The specific parameters of moringa seed extract include yield of 14.35%, organoleptic yellowish creamy color, distinctive smell of moringa seeds, thick shape and bitter taste, dissolved compounds in water solvent 70,40% ± 0,50% and dissolved compounds in ethanol 20.90% ± 0.87%. The non-specific quality parameters of moringa seed ethanol extract include a moisture content of 16,94% ± 0,72%, an ash content of 4.92% ± 0.08% and an insoluble acid ash content of 0.21% ± 0.01%. The research results of specific quality parameters of yield, identity, organoleptic, value of water-soluble compounds, soluble compounds in ethanol extract standard. The research results of non-specific parameters of moringa seed extract are total ash content and insoluble ash content of standard extract acids, while the results of moisture content do not meet the standard.